Progesterone: History, facts, and artifacts. (November 2020) - Di Renzo, Gian Carlo; Tosto, Valentina; Tsibizova, Valentina
Abstract: Progesterone and its related molecules are a crucial tool in modern clinical practice, particularly in the fields of reproductive medicine. Its history is old, but still under development. Presently, the pharmacokinetic and pharmacodynamic profiles of progesterone is well-known and knowledge on natural progesterone (P4) and other molecules with progestational activity, namely progestogens or gestagens, are improved and their interest is still alive. Topics of great and current interest are progesterone and its role in assisted reproductive protocols, threatened and recurrent pregnancy loss, threatened preterm birth with favorable results on pregnancy, and perinatal outcomes. Moreover, progesterone provides several other positive effects on women's health. This paper describes the main chronological steps that characterized the history of progesterone, where scientific research and clinical practice are arrived and WHICH are the future perspectives on this hormone with a "never-ending history."